Role of pure tone audiometry in assessing ossicular status in patients with mucosal type of chronic otitis media - Das, Deepthy; Sriraman, Gurumani; Rajasekaran, Valli (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2020)
Background: Chronic suppurative otitis media (CSOM) is the disease of the middle ear cleft, which presents as hearing loss and ear discharge. This study aimed to assess the role of pure tone audiometry (PTA) in analysing the ossicular erosion in mucosal type of CSOM subjects. Methods: The current cross-sectional study was conducted among 60 people with mucosal CSOM. Preoperative hearing was assessed by PTA. The surgeries were done and intra operative ossicular status were recorded. IBM SPSS 20 software was used for the analysis. Student t-test was used to correlate ossicular status and PTA findings. Results: Among 60 subjects, 12 (20%) patients had eroded incus and 53 (88.3%) had normal stapes. The malleus was preserved in all patients. The result of our study showed that an average ABG of 58 dB at 500 Hz, 47 dB at 1 kHz, 41 dB at 2 kHz and 41 dB at 4 kHz in patients with ossicular erosion. ABG for 500 Hz and 1 kHz were statistically significant for eroded incus. ABG for 500 Hz, 1 kHz, 2 kHz and 4 kHz were all statistically significant for eroded stapes. Conclusions: There is a significant difference between the PTA findings at different frequencies between intact and eroded ossicular chain. Pre-operative ABG helps us to assess the status of incus and stapes.